The socioeconomic context of stigma: examining the relationship between economic conditions and attitudes towards people with mental illness across European countries - Pybus, Katie; Pickett, Kate E.; Lloyd, Charlie; Wilkinson, Richard (Frontiers in Epidemiology, 2023)
Efforts to reduce the stigma associated with mental illness have intensified over the past thirty years with a particular focus on improving public attitudes. Difficult economic circumstances can be harmful to intergroup relations, but little is known about whether there is a relationship between socioeconomic conditions and attitudes towards people with mental illnesses. Random effects logistic regression modelling was employed to explore the relationship between individual financial circumstances, contextual socioeconomic factors and difficulty speaking to a person with a significant mental illness across European countries. Lower GDP per capita and higher income inequality at the country level, alongside individual financial difficulties, were each associated with a greater likelihood of reporting difficulty speaking to a person with a significant mental illness. Micro and macro-economic factors are associated with public attitudes towards people with mental illness across Europe. With prolonged economic instability predicted over the coming years in Europe it is important that these findings are taken into consideration when designing mental health and social policies, in order to safeguard the progress that has been made in reducing mental health stigma to date.